2006
DOI: 10.1007/s10750-006-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of proteinaceous material in the Florida coastal Everglades

Abstract: Dissolved organic nitrogen (DON) is the least known component of the nitrogen cycle, in part as a result of the lack of adequate analytical methods for its molecular characterization. In this study proteinaceous material in DON, collected at six geomorphologically different sites in the Florida coastal Everglades, was characterized by amino acid analysis and protein gel electrophoresis. The amino acid composition of the samples suggests that the canal DON was more degraded and subject to higher microbial input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In contrast, LMW‐DON is likely to associate with fine particles, and, indeed, only about 40% was present in coarse particles. Wedyan and Preston [2008], and Jones et al [2006] reported that LMW‐DON is composed of marine‐derived amino acids and derivatives of low molecular weight proteins. The results suggest that aerosols derived from sea spray have a major influence on the distribution of LMW‐DON in atmospheric particles, but experimental confirmation of this suggestion is required.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, LMW‐DON is likely to associate with fine particles, and, indeed, only about 40% was present in coarse particles. Wedyan and Preston [2008], and Jones et al [2006] reported that LMW‐DON is composed of marine‐derived amino acids and derivatives of low molecular weight proteins. The results suggest that aerosols derived from sea spray have a major influence on the distribution of LMW‐DON in atmospheric particles, but experimental confirmation of this suggestion is required.…”
Section: Resultsmentioning
confidence: 99%
“…5.3 (Ex: 275 nm; Em: 335 nm). Since the MW of proteinaceous materials might be different from other materials such as tannins, producing the protein-like peak (T-peak: Ex 280 nm; Em 325 nm) Hernes and Hedges, 2004;Jones et al, 2006), I applied SEC to determine the distribution of the protein-like fluorescence along the molecular weight continuum (Fig. 5.4).…”
Section: Preliminary Finding On Free Form Gallic Acid In Flocculent Smentioning
confidence: 99%